Group- based quantitative structural activity relationship analysis of B-cell Lymphoma Extra Large (BCL-XL) inhibitors - Abdul Samat, Nadia Hanis; Mohammed Abdulkader, Abdul Rahman; Mohamed, Farahidah; Abdullahi, Abubakar Danjuma (International Journal of Pharmacy and Pharmaceutical Science, 2014)
B-cell Lymphoma Extra Large (Bcl-xL) belongs to B-cell Lymphoma two (Bcl-2) family and owing to its anti-apoptotic role in many cancers, is proven to be an attractive target for anti-cancer therapy. Different classes of potent anti-Bcl-xL small molecules inhibitors have been discovered, and both three-dimensional (3D) and two-dimensional (2D) Quantitative Structural Activity Relationship (QSAR) approaches have been used to study and predict the biological activities of new inhibitors prior to their synthesis. Objectives: This study was aimed to generate new candidate small inhibitory molecules against Bcl-xL by using G-QSAR analysis of known Bcl-xL inhibitors. Methods: In the present study, we used group-based QSAR (G-QSAR)—a novel fragment-based method—to develop QSAR models from known BclxL inhibitors. A set of Bcl-xL inhibitors adopted from extant literature was fragmented into three common fragments, and a pool of 214 descriptors was calculated for each one. Results: Two models were obtained by using different combination of variable selection and model building method; stepwise-multiple linear regression (STP-MLR) and simulated annealing-multiple linear regression (SA-MLR). STP-MLR was found to be the best mode, with r2 = 0.80, q2 = 0.70 and predictive r2 = 0.87. Conclusion: The G-QSAR results indicate that the generated models are statistically significant and can be used for design and generation of new potent inhibitors.